Self-Initiated Expatriation (SIE) and Older Women: Motivations, Experiences and Impacts - Myers, Barbara (Auckland University of Technology, 2016)
Since 1893 when New Zealand women were the first in the world to win the right to vote, they have persisted in their groundbreaking ways. New Zealand women have been Prime Ministers, Governor General, Speaker of the House of Representatives and Attorney General. Currently a New Zealand woman is Chief Justice and a former Prime Minister Helen Clarke holds the third highest position at the United Nations. This study continues this trail blazing tradition with a focus on a number of older New Zealand women who have challenged the male norm of continuous and linear careers (Myers, 2011; Sabelis & Schilling, 2013) and the neoliberal expectation of an extended working life (Rudman, 2006). Anecdotal evidence suggests these ‘ordinary’ New Zealand women have effected ‘extraordinary’ life change as a result of exiting their established working lives to undertake self-initiated expatriation (SIE), a period of extended travel and work overseas (Doherty, Richardson, & Thorn, 2013a; Suutari & Brewster, 2000). This study draws on ‘older workers’, ‘population ageing, ‘careers’ and SIE research literatures. Four specific research objectives funnel the enquiry into the SIE phenomenon: the motivations, experiences, and triggers for SIE; the actual SIE work and personal experiences; whether SIE facilitates career and personal development; and whether SIE affords older women an opportunity to reflect on, clarify and enact longer term career and life-path goals. Fundamental to this study is the ontological assumption that the world is open-ended and socially constructed. Subjectivism was core to the research process. Thus, I adopted a reflexive and interpretive methodology and carried out 21 in-depth life story interviews. To ensure the integrity of ‘narrative inquiry’, I developed a five-step analytical framework and present the findings at four levels of analysis in a cycle of storying and re-storying. Firstly, each of the 21 interpretive life stories are documented. Secondly, five interpretive ‘journey’ themes are presented to facilitate an understanding of the participant’s process of transition. Thirdly, a number of general themes are drawn out which link explicitly to the research objectives and fourthly I draw on key insights from all levels to develop a collective ‘personal experience’ narrative (McCormick, 2004). Findings indicate that escape, unfinished business and the search for excitement were key SIE motivations. Enhancing career prospects were not an explicit driver. Individual SIE highlights were the cultural experiences and relationships developed through travel and work and unexpectedly, participants developed considerable career capital. They developed significantly at a personal level, clarified their values and priorities, and began to realise that different life-paths were open to them that were rich with possibilities. Post-SIE, the participants’ lives continued to evolve. Initial work experiences reinforced earlier pre-SIE disillusionment within the organisational context. Many participants eschewed paid work, and took on university studies and unpaid roles where they felt more valued and autonomous. Economic imperatives no longer shaped participant’s lives, and for those who worked, it was invariably a stepping stone towards a more holistic and authentic life-path. Within the literatures of older workers, SIE and careers, work remains at the core of the discussion. This study contributes to understanding intersections of age and gender by studying women’s experiences and the range of different meanings they attribute to work outside the usual structures of work and life. The participants in this research reflect a different way of being that is no longer tied to or centred around an economic model. I argue for an interdisciplinary and life-course approach to provide a more holistic and less work-centric understanding of SIE and career. This broad view better addresses the complexity and heterogeneity of later life transition and change. Like the pioneering women suffragettes, the participants in this research were also ‘path finders’, and for them SIE was a time for refocus, renewal and rejuvenation, symbolising a significant shift in their ‘ways of being’ where the new ‘retirement’ has become ‘rewirement’.
Keywords: SIE; Older women; Careers; Adult development